1995
DOI: 10.1002/jqs.3390100403
|View full text |Cite
|
Sign up to set email alerts
|

Patterned fen development in northern Scotland: Hypothesis testing and comparison with ombrotrophic blanket peats

Abstract: Charman, D. 1995. Patterned fen development in northern Scotland: hypothesis testing and comparison with ombrotrophic blanket peats.ABSTRACT: Patterned fens are part of the diverse Holocene peatland landscape of the Flow Country, northern Scotland. Their present vegetation and morphology allies them with boreal systems in Scandinavia and North America. However, previous work has shown that their mode of formation is rather different and has suggested a developmental model in which the poor fens have formed onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…These data are also consonant with the bog-wide and small-scale changes recorded by Barber (1981), Smith (1985), Wimble (1986) and Svensson (1988b), as well as in blanket bogs by Moore (1977), Smart (1982), Charman (1995) and by Tallis (1995Tallis ( , 1997. Although there is evidence that not all cores taken from bogs show more or less simultaneous changes (e.g.…”
Section: Implications and Recommendationssupporting
confidence: 85%
“…These data are also consonant with the bog-wide and small-scale changes recorded by Barber (1981), Smith (1985), Wimble (1986) and Svensson (1988b), as well as in blanket bogs by Moore (1977), Smart (1982), Charman (1995) and by Tallis (1995Tallis ( , 1997. Although there is evidence that not all cores taken from bogs show more or less simultaneous changes (e.g.…”
Section: Implications and Recommendationssupporting
confidence: 85%
“…Under these conditions, some peatlands could sequester more C (Charman et al, 2013), while others could turn into C sources and degrade (Ise et al, 2008;Fan et al, 2013). Permafrost peatlands are sensitive ecosystems and respond quite rapidly to temperature change and other aspects of climate (Christensen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, while some sites in this region are reported as being quite productive (21.3 ± 3.7 g C m −2 yr −1 ; Anderson, 2002), long-term CAR estimates are available for relatively few sites (Charman, 1995;Anderson, 1998), making a comparison difficult. The points that fall in the British Isles showed lower modelled LARCA (12-14 g C m −2 yr −1 ) values than the observed literature range, indicating shortcomings in the simulation of local hydrological conditions or a possible bias in the climate forcing of our model.…”
Section: Scandinavia and Europe (Zones A And B)mentioning
confidence: 99%
“…Future investigations could consider the role of other topographic variables. Stratigraphic studies of blanket peatland have shown that underlying topography is often more complex than surface topography causing local variability in depth (Tallis, 1991 and Charman, 1992, 1995). As surface topographic values were used, underlying variability would not have been represented in this study, and this may be an additional source of error.…”
Section: Discussionmentioning
confidence: 99%